Ways to Effectively Organize the Financing of the Education System - Kimsanboyeva Maftuna Bakhodirovna (Genius Journals, 2022)
The article draws conclusions and recommendations for improving the efficiency of the education system of Uzbekistan, based on the study of the education system of some countries and the specifics of their funding. The income and cost classification of the education system is also analyzed, and the article presents the views of scholars on the financing of the education system.
Keywords: Education; Funds Of Budget; University; Financing Of Education Systems